2017
DOI: 10.18632/oncotarget.16888
|View full text |Cite
|
Sign up to set email alerts
|

Combined efficacy of C-reactive protein and red blood cell distribution width in prognosis of patients with culture-negative infective endocarditis

Abstract: ObjectiveTo evaluate the combined effect of C-reactive protein (CRP) and red blood cell distribution width (RDW) on the prediction of in-hospital and long-term poor outcomes in patients with blood culture-negative infective endocarditis (BCNE).ResultsPatients with high CRP and high RDW has the highest incidence of in-hospital death (2.3% vs. 7.8% vs. 5.6% vs. 17.5%, P < 0.001). CRP > 17.8 mg/L (odds ratio [OR]=2.41, 95% confidence interval [CI], 1.06–5.51, P = 0.037), RDW >16.3 (OR = 2.29, 95% CI, 1.10–4.77, P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
0
7
0
1
Order By: Relevance
“…Several studies proved the predictive value of CRP for IE outcome, namely, in monitoring antimicrobial treatment. Its progressive decrease can suggest a favorable response, while persistent high values suggest complications and/or antibiotic resistance and induce the need for further investigations [ 20 , 21 ]. Our analysis also showed a good predictive value of high CRP levels for a negative outcome of disease.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies proved the predictive value of CRP for IE outcome, namely, in monitoring antimicrobial treatment. Its progressive decrease can suggest a favorable response, while persistent high values suggest complications and/or antibiotic resistance and induce the need for further investigations [ 20 , 21 ]. Our analysis also showed a good predictive value of high CRP levels for a negative outcome of disease.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated RDW is associated with an increased risk of age-related diseases and mortality; moreover, RDW reflects overall inflammation because it is associated with overall and disease-specific mortality risk 41 , 42 . Veeranna 43 and Wei 44 performed comparative analyses of RDW and CRP for mortality prediction in patients with coronary heart disease and infectious endocarditis, respectively. They concluded that RDW, and not CRP, was associated with mortality, independent of traditional risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Cellular senescence is an irreversible process. Unlike traditional biomarkers of acute inflammation, RDW is a valid indicator of senescence because it is not affected by cases of acute inflammation, such as infectious diseases; more so, it increases over time without large fluctuation, and it has a low reversibility 43 , 44 . The study results indicate that age-related physical changes in body composition, such as skeletal muscle loss and fat accumulation, are mechanisms of senescence that occur based on chronic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The mortality rate for methicillin-resistant SAB (MRSAB) is 32% and for methicillin susceptible SAB (MSSAB) is 14%, both higher than in other infections. Wei found that increased CRP and red blood cell distribution width, especially in combination, were associated with in-hospital mortality in patients with blood culture-negative infective endocarditis [14]. Other biochemical markers such as troponin, B-Type Natriuretic Peptide and D-dimer are reliable prognostic biomarkers associated with adverse outcomes in patients with IE [15][16][17].…”
Section: Discussionmentioning
confidence: 99%